The Civic and Social Dimensions of Food Production and Distribution in Alternative Food Networks in France and Southern Brazil - Lamine , Claire; Darolt, Moacir; Brandenburg, Alfio (The International Journal of Sociology of Agriculture and Food, 2012)
This article offers comparative insight into alternative food networks, based on French and Brazilian case studies. Looking at a series of initiatives, such as producer–consumer networks (Ecovida in Southern Brazil, AMAP in France), collective producer shops, farmers’ markets, and school provisioning schemes, we analyse the modes of coordination and decision-making that are articulated and the roles of the different actors involved. We show that the growing role of consumers and producers in these food networks, not only as individuals but also as citizens often involved in civil society organizations, can directly influence changes in public policy and the forms of agriculture practised, thereby leading to a better integration of the civic and social dimensions of food production and distribution. In both countries alternative food networks have strongly contributed to the legitimization of agro-ecology, although this is framed significantly by national specificities surrounding the institutionalization of ecological agriculture. In France this process focuses on organic agriculture, while it is more diverse in Brazil. Finally, we show that civic food networks’ influence on public policy partly relies on the alliances these networks are able to develop amongst themselves and with more institutional actors. We conclude with a discussion about food democracy.